Roles and barriers of community pharmacy professionals in the prevention and management of noncommunicable diseases in Ethiopia: a systematic review - Sendekie, Ashenafi Kibret; Belachew, Eyayaw Ashete; Limenh, Liknaw Workie; Chanie, Gashaw Sisay; Bizuneh, Gizachew Kassahun; Dagnaw, Abera Dessie; Tadesse, Yabibal Berie; Gete, Kalab Yigermal; Tamene, Fasil Bayafers; Abate, Biruk Beletew (Frontiers in Public Health, 2025)
BackgroundPharmacists play a crucial role in the prevention and management of noncommunicable diseases (NCDs) by providing medication therapy management, disease monitoring, and patient education. However, existing evidence on the roles and barriers of community pharmacy professionals (CPPs) in preventing and managing noncommunicable diseases in Ethiopia remains inconsistent. This study aimed to synthesize available research on the roles and barriers faced by CPPs in noncommunicable diseases prevention and management among adults in Ethiopia.MethodsA comprehensive literature search using four electronic databases, including Scopus, Medline/Ovid, Web of Science, and Embase was conducted. In addition, further studies were identified through Google Scholar searches and manual reference searches. The review included studies published before 30 July 2024 without any limitations on the starting time.ResultsA total of 15 studies were included in this review, with most studies focused on CPPs’ involvement in the prevention and management of non-specific NCDs and diabetes. CPPs were involved in a variety of roles in the prevention, screening, and management of NCDs. Their scope of practice included providing health promotion on lifestyle changes and nutrition, medication therapy management, chronic disease screening, disease-specific counseling, and general self-care promotion. This review identified different barriers CPPs encountered during their provision of NCD care, which were mainly categorized under four classes: CPP-related, pharmacy setting and working environment-related, policy/healthcare system-related, and patient/public-related barriers.ConclusionCPPs provide a wide range of services, from health promotion to disease screening and management of noncommunicable diseases. However, potential barriers such as limited training and resources, lack of reimbursement for noncommunicable disease services, and inadequate integration into the healthcare system can limit them from effectively providing these services. Addressing these barriers is essential to enhance the role of CPPs in noncommunicable diseases prevention and management.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023486384, Unique Identifier: CRD42023486384.